Kajian Teologis Dogmatis Terhadap Pemahaman Kristologi Orang Kawanua - Sompe, Del Gesscael Natewangun; Tombeng, Ineke Marlien (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This study aims to describe the understanding of the Christology of the Kawanua people in the Providensia Tanggerang congregation and how it is in accordance with the teachings of the church and GMIM Christology. Informants have been selected from among the members of the congregation and special servants using purposive sampling. The transcripts were then analyzed using a phenomenological approach. The participants' personal experiences are described as follows: 1. Most of the people in the GMIM Providentia Tangerang congregation understand Jesus Christ as Lord and Savior, the Helper during their time abroad, and who has united them with their fellow people to worship together within the scope of GMIM. 2. Regarding its conformity with the teachings of the church and GMIM christology, it can be seen that everyone understands who Jesus is, but there are still those who do not understand Jesus' position in the relationship of the Trinity. This description can serve as input for the Christian Evangelical Church in Minahasa to improve the quality of its ministry, so that the faith life of its congregation members becomes more clearly centered on knowing who Jesus Christ is.